2005
DOI: 10.1016/j.jviromet.2005.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Virus-inducible reporter genes as a tool for detecting and quantifying influenza A virus replication

Abstract: SummaryThe use of influenza A virus-inducible reporter gene segments in detecting influenza A virus replication was investigated. The RNA polymerase I promoter/terminator cassette was used to express RNA transcripts encoding green fluorescence protein or firefly luciferase flanked by the untranslated regions of the influenza A/WSN/33 NP segment. Reporter gene activity was detected after reconstitution of the influenza A virus polymerase complex from cDNA or after virus infection, and was influenza A virus-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
103
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(105 citation statements)
references
References 44 publications
(47 reference statements)
1
103
0
1
Order By: Relevance
“…10 ng pRL-SV40 constitutively expressing Renilla luciferase was added to normalize transfection efficiency. It was previously shown that expression of the firefly luciferase reporter gene correlates with the activity of the reconstituted polymerase complex (45).…”
Section: Methodsmentioning
confidence: 99%
“…10 ng pRL-SV40 constitutively expressing Renilla luciferase was added to normalize transfection efficiency. It was previously shown that expression of the firefly luciferase reporter gene correlates with the activity of the reconstituted polymerase complex (45).…”
Section: Methodsmentioning
confidence: 99%
“…The authors are grateful to Professor Dr Gert Zimmer (University of Hannover, Germany) for providing PKC expression constructs, Professor Dr Erich Hoffmann (UTMB, TX, USA) for providing a set of influenza virus expression constructs, the Company Apath LLC (St Louis, MO, USA) for providing the influenza GFP reporter construct pHH21-NP-UTRhi-eGFP (Lutz et al, 2005), Dr Klaus Korn and Helga Bischoff (Institute of Clinical and Molecular Virology, University of Erlangen-Nuremberg) for support with the influenzaspecific qRT-PCR and excellent technical assistance, respectively, Dr György Keri (Vichem Chemie Research Ltd, Budapest, Hungary) for supplying a panel of protein kinase inhibitors, Professor Dr Michael Stürzl and Andreas Konrad (Institute of Experimental Surgery, University of Erlangen-Nuremberg) for methodical collaboration, Sabine Rechter and Stephanie Platzer for help in establishing the influenza reporter system and IVKAs and Jens Milbradt for scientific discussion. This work was supported by the ELAN Fonds of the University of Erlangen-Nuremberg and the Deutsche Forschungsgemeinschaft (grant MA 1289/4-1).…”
Section: Acknowledgementsmentioning
confidence: 99%
“…Transient transfection of 293T cells was performed in 12-well plates at a confluence of 70-90 % (seeding cell number 2.5610 5 ) by using Lipofectamine 2000 (Invitrogen). The influenza-specific green fluorescent protein (GFP) construct pHH21-NP-UTRhi-eGFP (Lutz et al, 2005) served as a reporter of viral replication. One day post-transfection with the reporter construct, cells were infected with influenza A/WSN/33 virus and were subsequently cultivated in the presence or absence of Gö6976 (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1B). We explored the inhibition activities of the antiinfluenza compounds using three additional assays: influenza neuraminidase, influenza entry using the pseudotyped virus expressing influenza hemagglutinin, HApp (17), and the cell-based reporter assay for the influenza RdRP (18). Except for the known neuraminidase inhibitors Oseltamivir and Zanamivir, no other compounds are inhibitory to the influenza neuraminidase activity.…”
mentioning
confidence: 99%